Grandmothers unite: Sharing wisdom and advocacy for the wellbeing and success of foster children - Musetsho, Mulalo; Sesoko, Mimie; Leburu, Goitseone (Social Work/Maatskaplike Werk, 2025)
A foster care awareness programme (FCAP) can play a critical role in strengthening caregivers’ understanding of ways to support vulnerable children under their care. Despite the significance of such programmes, grandmother-headed families face challenges such as managing indiscipline, establishing family values, parenting and addressing health risks. Moreover, there is lack of literature on grandmothers’ experiences of FCAPs as an intervention strategy. Using a qualitative approach and a phenomenological research design, 10 grandmothers were purposefully recruited with the aim of developing an in-depth understanding of their experiences of foster care awareness programmes as an intervention strategy. Data were collected through individual, face-to-face semi-structured interviews and analysed using six steps of thematic data analysis. The findings revealed that grandmothers shared experiences and learnt from one another, leading to significant changes in their families' lives, particularly in communication, parenting and financial management. These changes contributed to emotional stability within their households. The study recommends extending foster care programmes to include joint and individual sessions for foster children and their parents. Additionally, social workers are encouraged to invest more time in group and community work as alternative strategies to traditional casework.